2021
DOI: 10.3390/v13010139
|View full text |Cite
|
Sign up to set email alerts
|

RSV and HMPV Infections in 3D Tissue Cultures: Mechanisms Involved in Virus-Host and Virus-Virus Interactions

Abstract: Respiratory viral infections constitute a global public health concern. Among prevalent respiratory viruses, two pneumoviruses can be life-threatening in high-risk populations. In young children, they constitute the first cause of hospitalization due to severe lower respiratory tract diseases. A better understanding of their pathogenesis is still needed as there are no approved efficient anti-viral nor vaccine against pneumoviruses. We studied Respiratory Syncytial virus (RSV) and human Metapneumovirus (HMPV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…CPE in primary HAEC dif often resembles the natural situation more closely compared to continuous cells. HRSV offers a good example: in continuous cell lines it forms big syncytia (hence the name), but in primary HAEC HRSV forms little to no syncytia, which is in line with observations in vivo (both animal models and humans) ( 48 , 122 , 129 , 168 170 ). A clinical observation in HRSV disease is neutrophil inflammation, which is involved in severe HRSV disease.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…CPE in primary HAEC dif often resembles the natural situation more closely compared to continuous cells. HRSV offers a good example: in continuous cell lines it forms big syncytia (hence the name), but in primary HAEC HRSV forms little to no syncytia, which is in line with observations in vivo (both animal models and humans) ( 48 , 122 , 129 , 168 170 ). A clinical observation in HRSV disease is neutrophil inflammation, which is involved in severe HRSV disease.…”
Section: Discussionsupporting
confidence: 73%
“…In response to influenza virus infection, similar cytokines, mainly IL-1β, IL-6 and IL-8, were produced in HAEC dif from different parts of the RT ( 114 , 116 118 ). For HRSV and HMPV infections it has also been shown that similar cytokines, predominantly type I and/or type III IFN, are produced in HAEC dif (nasal, bronchial and small airway) ( 123 , 126 132 , 168 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to study the effect of respiratory viruses on SARS-CoV-2 replication in multiple versus single infections, sequential infections were performed as previously described [ 17 , 18 ]. In a first set of co-infection assays ( Figure 1 A, upper panel), RV, IAV and IBV pre-infected tissues were inoculated with SARS-CoV-2 48 h after the primary (first) infection.…”
Section: Resultsmentioning
confidence: 99%
“…For dual infections, similar protocol was used for the second infection 1 or 2 days after the first one. In order to study the involvement of interferon (IFN), similar dual assays were repeated where a mixture of anti-type I neutralizing antibodies diluted 1/50 (39000-1, PBL Assay Science TM , Piscataway, NJ, USA) and 10μg/mL of anti-IFN-λ1 (MAB15981-100, RandD, Minneapolis, MN, USA), were added in the basolateral medium as previously described [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%